A 15 ka lake water δD record from Genggahai Lake, northeastern Tibetan Plateau, and its paleoclimatic significance. (July 2016) - Rao, Zhiguo; Qiang, Mingrui; Jia, Guodong; Li, Yunxia; Dan, Dan; Chen, Fahu
Highlights: Genggahai mid-chain and long chain n -alkanes are derived mainly from aquatic plants. The δD n -alkanes data recorded δDLW variation. Genggahai δDLW is controlled mainly by local δDMW and lake surface evaporation. Genggahai δDLW record provides a record of ISM intensity. Abstract: The mid-chain and long chain n -alkanes in sediments of Genggahai Lake, on the northeastern Tibetan Plateau, have been assigned as being predominantly from aquatic plants. Thus, at the lake, compound specific hydrogen isotopic data for mid- and long chain n -alkanes (δD n -alkanes ) are indicators of the variation in lake water δD (δDLW ). Genggahai δDLW is determined by the local meteoric water δD (δDMW ) and by lake surface evaporation, as evidenced by modern observational data and the broad correlation between Genggahai δDLW and average lake water depth during the past 15 ka, with more negative δDLW values corresponding to greater average water depth. As demonstrated by the mid- and long chain δD n -alkanes data, the most negative interval of Genggahai δDLW was during the early Holocene. An overall trend towards more positive values from the early to the late Holocene clearly indicates the long term evolutionary history of local δDMW, which could be related to the intensity of the Indian summer monsoon (ISM) via the "rainfall amount effect". Therefore, the record of δDLW at Genggahai during the past 15 ka, which resembles that of stalagmite δ 18 O records from the core ISM region, apparently reflects the long term evolution of ISM intensity. Furthermore, several short-term positive excursions in Genggahai δDLW values during the late Holocene reflect enhanced lake surface evaporation via an "isotopic enrichment" mechanism that apparently resulted from periods of weakened ISM intensity. Our results highlight the fact that unambiguous source determination of n -alkanes is vital for determining the paleoclimatic significance of lacustrine δD n -alkanes data.